Investigations of burial practices and the concept of the afterlife in the archaeology of Lithuania. Historiographical aspect - Petrauskas, Gediminas (Archaeologia Lituana, 2015)
Investigations of burial practices in Lithuania started in the middle of the 19th century. Since then, concepts of burial, death and the afterlife were brought up in studies (popular and scientific articles, publications and monographs) of many antique lovers, self-educated relic collectors and researchers of prehistoric and historical burial practices. The first attempts to estimate and interpret burial practices originated from the fieldwork practice, although they lacked a broader theoretical base and preparation. A materialistic concept of the developing archaeology, concentration in collecting and filing of artefacts found at burial sites influenced a superficial and often poorly based interpretation of the past society. The only exception was a study by Jonas Basanavičius (1998, pp. 13–91) in the early 1900s. This was one of the first scientific works that examined the concept of the afterlife of ancient Lithuanians. In the study, however, folklore and mythological sources were weakly associated with the archaeological material. First thorough studies of burial practices, death and the afterlife were published in the 1940s by Marija Alseikaitė- Gimbutienė (1942; 1942 š; 1943 a; 1943 b; 1946 š), known as Marija Gimbutas in the West. A broad researcher’s approach of archaeology was formed, influenced by her professors, a linguist Antanas Salys and an archaeologist Jonas Puzinas, also, by works of J. Basanavičius (Fig. 1–2). For the first time, M. Alseikaitė-Gimbutienė investigated burial practices, the concept of the afterlife and the relationship between the living and the dead through the interdisciplinary context of history, folklore and ethnology. Archaeology was brought to light as a national science, part of a broader Lithuanian philology. In the 2nd half of the 20th century, due to the Soviet occupation of Lithuania, followed by cultural and academic isolation, imposed censorship and the “iron curtain”, the archaeology of Lithuania was cut off from Western archaeological developmental processes. The interpretation of burial practices remained within the frame of Marxist-Leninist ideology. Although extensive archaeological investigations of burial sites were performed and a lot of empirical data were collected during that period, archaeological publications lacked a broader assessment and reasoned interpretation of burial practices. At the beginning of the 21st century, transformation took place in interpreting burial practices. Various aspects of death, burial practices and the afterlife were investigated in studies. That included a broad perspective of archaeology, ethno-logy, folklore, mythology and comparative religion, the latest hypotheses and research data by Lithuanian and foreign researchers. Investigations of burial practices were gradually becoming an object of broad interdisciplinary studies. Burial practices, a custom of burying the dead with grave goods, relationship between the living, the dead, deities and the environment – all had its own place, meaning and explanation. Therefore, in the investigations of death, burial practices and the concept of the afterlife it is essential to analyze the behaviour and the ideology of the past society, to search links among archaeology, mythology, folklore and other disciplines. Broad interdisciplinary studies are an objective of every researcher of burial practices. Translated by the author, the translation revised by Danguolė Vertelka